A grid-free global optimization algorithm for sound sources localization in three-dimensional reverberant environments. (1st April 2023) - Zhai, Qingbo; Ning, Fangli; Deng, Zongling; Hou, Hongjie; Li, Jing; Wei, Juan; Li, Baoqing
Abstract: In this work, a new grid-free global optimization algorithm that combined the image source model(ISM) and state transition algorithm(STA) was proposed to realize the sound source localization in reverberant environments. The simulation results show that only first-order mirror sources being kept can ensure localization accuracy. Compared with de-reverberation beamforming, the localization results of the proposed algorithm have no sidelobes and smaller mainlobes. Compared with the differential evolution(DE) algorithm, STA can converge to smaller fitness values, which can achieve more accurate sound source localization in reverberant environments. Meanwhile, the proposed algorithm can be applied to both single-source and multi-source localization in practical scenarios. The experimental results show that the proposed algorithm can locate the sound source accurately in reverberant environments. Highlights: A 3D grid-free de-reverberation sound sources localization algorithm is proposed. It shows no sidelobes and smaller mainlobes than the de-reverberation beamforming. It achieves more accurate results than the differential evolution algorithm.